ACCELERATION OF BALI TOURISM RECOVERY IN FACING THE GLOBAL ECONOMIC RECESSION IN 2023 - Made Heny Urmila Dewi; Ni Putu Martini Dewi (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Global economic pressures have been felt by many countries at the end of 2022. The weakening global economic environment, both directly and indirectly, has the effect on Indonesia’s economic performance, including Bali. This condition poses a threat of an economic recession in 2023. The objectives of this study are: (1) to examine the development conditions of Bali’s tourism sector in facing the threat of a global economic recession in 2023, and (2) to examine strategies for accelerating the recovery of Bali’s tourism sector so that it can survive the global economic recession in 2023. This research was conducted in the Province of Bali. The Province of Bali was chosen as the study location because it is a tourism center that is significantly affected by this economic recession. The data analysis methods used in this study are as follows: (1) descriptive analysis, which is used to examine economic growth, economic performance, and the performance of Bali’s tourism sector, and (2) policy analysis. The results of the study show that: (1) Bali’s economic development in 2023 is in a conducive condition despite the issue of a global recession, (2) Bali’s economic development in 2023 is still driven by improved performance in business sectors related to tourism, (3) several actions that need to be taken to accelerate the recovery of Bali’s tourism sector are maintaining the uniqueness of attractions, accessibility, promotion, and infrastructure, and (4) strategies that need to be implemented so that tourists visiting Bali feel safe and comfortable are by applying high standards of sanitation, high standards of security, staycation, niche tourism, wellness tours, and virtual tourism.